2019
DOI: 10.3847/1538-4357/ab2461
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-epoch X-Ray Study of the Spiral Galaxy NGC 7331

Abstract: X-ray point sources in galaxies are dominated by X-ray binaries (XRBs) that are variables or transients and whether their variability would alter the X-ray luminosity functions (XLF) is still in debate.Here we report on NGC 7331 as an example to test this with 7 Chandra observations. Their detection limit is 7×10 37 erg s −1 in the 0.3 -8.0 keV energy range by assuming a power-law spectral model with a photon index of 1.7. We detected 55 X-ray sources. Thirteen of them are variables for which 3 of them are tra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 58 publications
1
2
0
Order By: Relevance
“…The inferred best-fitting parameters as well as absorbed and unabsorbed fluxes are reported in Appendix B, Table 3. Our measurements are consistent with the X-ray analysis presented in Jin & Kong (2019).…”
Section: Soft X-ray Observations With the Cxosupporting
confidence: 92%
“…The inferred best-fitting parameters as well as absorbed and unabsorbed fluxes are reported in Appendix B, Table 3. Our measurements are consistent with the X-ray analysis presented in Jin & Kong (2019).…”
Section: Soft X-ray Observations With the Cxosupporting
confidence: 92%
“…Initially discovered by William Herschel in 1784, NGC 7331 has been widely studied over the past 200 years. Located at a distance of 14.7 Mpc (Freedman et al 2001), NGC 7331 has been included in a large number of galaxy surveys and has been mapped at wavelengths spanning Xrays (Jin & Kong 2019) to millimeter CO lines (Leroy et al 2009). Studies of NGC 7331 have found that it has a large molecular ring and L FIR ∼ 2 × 10 10 L (Thilker et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Fabbiano (1989Fabbiano ( , 2006 present an extensive summary of the X-ray source populations in nearby spiral galaxies. X-ray properties such as X-ray luminosity, hardness ratios, and variability can be utilized to identify and study X-ray binaries (Kaaret et al 2001;Prestwich et al 2003;Luan et al 2018;Jin & Kong 2019;Sell et al 2019).…”
mentioning
confidence: 99%